Challenges faced by micro, small, and medium lodgings in Kelantan, Malaysia - Abdul Aziz, Yuhanis; Awang, Khairil Wahidin; Samdin, Zaiton (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The primary objective of this study is to identify the unique business characteristics of micro, small and medium (MSM) enterprises as well as to address issues and challenges faced by these enterprises in the hospitality and tourism business. This exploratory study employed semistructure face-to-face indepth interview methods for data collection. A total of 11 enterprises in Kelantan, Malaysia participated in the study. Nvivo was employed as a tool to analyse the data. The findings imply that MSM enterprises suffer from several obstacles such as financial constraint, high taxes, lack of state government support, the successor replacement and others. The study provides discussions on how hospitality and tourism enterprises can address the challenges faced by their business.